Analysis of Third-Generation Solar Cell Design with Physics of Semiconductor - Tin Swe, Hsu Myat; Ei Khin, Ei; Soe, Khaing Thandar; Win, Lei Lei Yin; Tun, Hla Myo; Pradhan, Devasis (Journal of Novel Engineering Science and Technology, 2024)
The paper presents the Analysis of Generation Solar Cell Design with Physics of Semiconductor. The research problem in this study is how to design a high-performance solar cell with novel semiconductor compounds that are fabricated in the laboratory based on the physical parameters. The approach to solving the proposed research problem is based on experimental studies through theoretical research in recent works. The first one is to develop the effective structure for solar cell design and the other is to develop the energy band structure of III-V compound-based third-generation solar cell. The simulation analyses were carried out with the help of MATLAB language. There are many steps to designing high-performance semiconductor devices for real-world applications. The results confirm that the numerical analyses of these two developments could be supported to estimate the outcomes of experimental studies without using real equipment in the laboratory.